Analysis of The Coporate Debt Situation Implication on Risk Company's Development - Yanko Hristozov (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2020)
High corporate indebtedness is a significant problem for companies' finances, often blocking their balance sheets, also difficult debt repayment can lead to insolvency. This is a problem not only for companies, but also for the economies of countries. The purpose of the study is to track changes in indebtedness for the period 2008-2018. Time limits are set due to access to statistical information and for most countries the latest data are for 2018. The base year is in line with the development of the financial and economic crisis to clarify its impact on indebtedness. The object of study are nonfinancial corporations, and the subject is an analysis of changes in their corporate debt. To achieve this goal, the following tasks are set: to choose an appropriate methodology, to study the literature on the subject, to compare the changes in the indebtedness of non-financial corporations in key countries in Europe and beyond. Based on the statement that due to the financial and economic crisis and the aggressive investment policy during the studied 11-year period, corporate debt increases significantly, and this puts at risk the company's development and the world economy.